Pengaruh Kepemimpinan Transformasional Terhadap Organizational Citizenship Behavior (OCB) Melalui Mediasi Kepercayaan Kepada Atasan dan Kepuasan Kerja Karyawan - Vira Adisty Febrika; Suhana Suhana (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine the influence of transformational leadership on OCB, trust in superiors, and employee job satisfaction. Research was also conducted to identify the influence of trust in superiors and employee job satisfaction on OCB and whether or not there is a mediating effect of trust and job satisfaction on the transformational leadership relationship and OCB. The study population is employees working at the Central Java Provincial Manpower and Transmigration Office with a sample of 100 respondents. Sampling was done using a simple random sampling technique. Taking research data by distributing questionnaires directly. Data analysis using the boostrapping method on the SmartPLS 4 software. The results of the study show the positive influence of transformational leadership on OCB, trust in superiors, and employee job satisfaction. Transformational leadership has a positive and insignificant impact on OCB but is significant on trust in superiors and employee job satisfaction. The variables of trust and job satisfaction have a positive and insignificant influence on OCB. In addition, trust in superiors plays a role in mediating the influence of transformational leadership on OCB. Employee job satisfaction also mediates the relationship between transformational leadership and OCB.